2023
DOI: 10.7759/cureus.37813
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Discontinuation of Renin Angiotensin-System Inhibitors in Patients With Advanced Chronic Kidney Disease: A Meta-Analysis

Abstract: Renin-angiotensin system inhibitors (RAS) inhibitors include angiotensin receptor blockers (ARBs) and angiotensin-converting enzyme (ACE) inhibitors decrease proteinuria, progression of chronic kidney disease (CKD), and protect against heart failure hospitalizations and cardiovascular events. There is uncertainty about the appropriate time for discontinuing ARB and ACE inhibitor treatment in patients with low estimated glomerular filtration rate (eGFR). In the present meta-analysis, we examined the effect of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition, the prevalence of hypertension was significantly lower in the early mortality group; however, the reason for this was unclear. It is possible that the use of renin–angiotensin–aldosterone system inhibitor (RAASI) reflects a reduction in mortality, and the low RAASI use in the early mortality group (36.1% in the early mortality group vs. 51.6% in the non-early mortality group) was associated with a low prevalence of hypertension during the retrospective data collection process 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the prevalence of hypertension was significantly lower in the early mortality group; however, the reason for this was unclear. It is possible that the use of renin–angiotensin–aldosterone system inhibitor (RAASI) reflects a reduction in mortality, and the low RAASI use in the early mortality group (36.1% in the early mortality group vs. 51.6% in the non-early mortality group) was associated with a low prevalence of hypertension during the retrospective data collection process 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Findings of a recent multicenter randomized study assigning 411 patients with advanced CKD to discontinuation or continuation of RAAS inhibitors found that discontinuation was not associated with a significant between-group difference in the long-term rate of a decrease in the eGFR [19]. Also, a recent meta-analysis found that the continuation of RAAS inhibitors may benefit patients with CKD [20]. Overall, data on the use of RAAS inhibitors and the course of renal function suggest that renal function is protected, at least in the non-acute state.…”
Section: Discussionmentioning
confidence: 99%
“…28,29,31 GLP-1, when administered as a 7-36 amide (an active form of GLP-1) at physiologic levels, also induces a significant reduction in circulating levels of angiotensin II, without corresponding changes in renin or aldosterone in healthy adults, an important finding given the well-established kidney-protective effects of RAS blockade. 31,32 The mechanism of angiotensin II suppression in this setting is not yet known. The natriuretic effect and suppression of angiotensin II, as described above, depends on GLP-1 receptor activation as demonstrated by the fact that these effects are abolished by coadministration of a GLP-1 receptor antagonist.…”
Section: Kidney Physiology and Glp-1mentioning
confidence: 99%